The Influence of Diabetes on Labor Induction with Dinoprostone Vaginal Inserts - Duffy, Jennifer Y.; Chau, Cindy; Raymond, Kyle; Rugarn, Olof; Wing, Deborah A. (American Journal of Perinatology, 2021)
Objective The aim of this study was to compare duration of labor induction between diabetic and nondiabetic women receiving dinoprostone vaginal insert (10 mg).Study Design This is a secondary analysis of two large randomized controlled trials using dinoprostone vaginal inserts for labor induction. We compare time to active labor, overall delivery, and vaginal delivery between diabetic and nondiabetic women undergoing induction of labor with a 10-mg dinoprostone vaginal insert.Results Diabetic women receiving dinoprostone vaginal insert had a longer time to onset of active labor, overall delivery, and vaginal delivery than their nondiabetic counterparts. There was no difference in abnormal labor affecting fetal heart rate pattern in diabetic women compared with nondiabetic women. The rates of neonatal hyperbilirubinemia were higher in diabetic women.Conclusion Diabetes may represent an independent factor associated with prolonged induction among women undergoing induction of labor with dinoprostone. Dinoprostone is well tolerated in both diabetic and nondiabetic women.Key Points
Keywords: dinoprostone; diabetes; induction; labor; prostaglandin